2008
DOI: 10.1111/j.1365-2745.2008.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation to biotic factors: reciprocal transplants of four species associated with aromatic Thymus pulegioides and T. serpyllum

Abstract: Summary 1.A plant producing secondary compounds may affect the fitness of other plants in the vicinity, and, likewise, associated plants may evolve adaptation to the presence of their 'chemical neighbour'. Species of the genus Thymus are aromatic plants, well known for their production of aromatic oils whose constitution is dominated by mono-or sesquiterpenes. A polymorphism for the production of the dominant terpene in the oil exists both within and between thyme species. 2. Here we examine the effects of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 63 publications
3
57
1
1
Order By: Relevance
“…Boudsocq et al 2012;and also Metlen et al 2012 for the modification of competitive interactions by leaf litter). In thyme communities, genetic variations in associated plant species for the sensitivity to thyme monoterpene have been found (Jensen & Ehlers 2010), and reciprocal transplant experiments on a number of associated species found that plants showed an adaptative response to their local thyme chemotype (Ehlers & Thompson 2004;Grøndahl & Ehlers 2008;Jensen & Ehlers 2010). Although individual plant species are able to adapt to their local thyme chemotype, and some species even performing significantly better on soil with than on soil without thyme monoterpene (Ehlers & Thompson 2004;Jensen & Ehlers 2010), it is less clear how this chemotype variation, and the potential for other species to adapt to local chemotypes, may impact upon the diversity of the entire community.…”
Section: H O W M a Y T H Y M E A F F E C T L O C A L S P E C I E S Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Boudsocq et al 2012;and also Metlen et al 2012 for the modification of competitive interactions by leaf litter). In thyme communities, genetic variations in associated plant species for the sensitivity to thyme monoterpene have been found (Jensen & Ehlers 2010), and reciprocal transplant experiments on a number of associated species found that plants showed an adaptative response to their local thyme chemotype (Ehlers & Thompson 2004;Grøndahl & Ehlers 2008;Jensen & Ehlers 2010). Although individual plant species are able to adapt to their local thyme chemotype, and some species even performing significantly better on soil with than on soil without thyme monoterpene (Ehlers & Thompson 2004;Jensen & Ehlers 2010), it is less clear how this chemotype variation, and the potential for other species to adapt to local chemotypes, may impact upon the diversity of the entire community.…”
Section: H O W M a Y T H Y M E A F F E C T L O C A L S P E C I E S Rmentioning
confidence: 99%
“…The phenolic monoterpenes, in general, have a more inhibiting effect on the germination and growth of plants than non-phenolic ones (Tarayre et al 1995). However, reciprocal transplant experiments showed that associated plants can adapt to their local thyme chemotype (Ehlers & Thompson 2004;Grøndahl & Ehlers 2008;Jensen & Ehlers 2010) performing better on soil containing their local monoterpene. Monoterpenes are also a dominant component of the essential oil in many other aromatic plants common to the Mediterranean flora (Thompson 2005); therefore, the effect of these compounds on the associated community may not only be restricted to thyme.…”
Section: Introductionmentioning
confidence: 99%
“…The traits underlying these patterns were not clear, but derive in part from indirect interactions mediated by soil microbes (19). Additionally, several studies of chemically divergent Thymus species have suggested that populations of cooccurring plant species may adapt to the particular Thymus chemotype with which they interact (20)(21)(22). Again, this adaptation may be partially mediated by soil properties or communities (20,23).…”
mentioning
confidence: 99%
“…Competitive outcome and relationships between functional traits and competitive ability may be strongly influenced by the choice of the competitor species (Wang et al 2010;Baron et al 2015). In natural conditions, community species composition and spatial structure determine the identities of interacting individuals, and the frequency of such interactions is a factor regulating local adaptation in competing species (Turkington 1989;Grondahl and Ehlers 2008;Lankau 2012;Abakumova et al 2016). To assess interspecific interactions in a realistic setting, we therefore conducted an experiment in which we selected 26 focal species characteristic of temperate grasslands and grew them in interspecific competition with a species they encounter as a common neighbour in their home community (Semchenko et al 2013).…”
mentioning
confidence: 99%